Mechanochromic Photonic Gels. (10th June 2013) - Chan, Edwin P.; Walish, Joseph J.; Urbas, Augustine M.; Thomas, Edwin L.
Abstract Polymer gels are remarkable materials with physical structures that can adapt significantly and quite rapidly with changes in the local environment, such as temperature, light intensity, electrochemistry, and mechanical force. An interesting phenomenon observed in certain polymer gel systems is mechanochromism – a change in color due to a mechanical deformation. Mechanochromic photonic gels are periodically structured gels engineered with a photonic stopband that can be tuned by mechanical forces to reflect specific colors. These materials have potential as mechanochromic sensors because both the mechanical and optical properties are highly tailorable via incorporation of diluents, solvents, nanoparticles, or polymers, or the application of stimuli such as temperature, pH, or electric or strain fields. Recent advances in photonic gels that display strain‐dependent optical properties are discussed. In particular, this discussion focuses primarily on polymer‐based photonic gels that are directly or indirectly fabricated via self‐assembly, as these materials are promising soft material platforms for scalable mechanochromic sensors.